2018
DOI: 10.1186/s13071-017-2605-7
|View full text |Cite
|
Sign up to set email alerts
|

Bionomic aspects of Lutzomyia evansi and Lutzomyia longipalpis, proven vectors of Leishmania infantum in an endemic area of non-ulcerative cutaneous leishmaniasis in Honduras

Abstract: BackgroundSome Lutzomyia species are the vectors of human leishmaniasis in the Americas. Visceral and cutaneous leishmaniasis are both endemic in the Pacific region of Honduras, but the non-ulcerative form is the more frequent clinical manifestation in this region, where Lutzomyia longipalpis is the most abundant and the only incriminated vector. Taxonomic identification and distribution studies of sand flies are important to understand the epidemiology and to control these neglected tropical diseases.ResultsH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 51 publications
0
22
0
2
Order By: Relevance
“…Additionally, behavioral characteristics of this species in the study area were described by Carrasco et al [7]. Recently, Mejía et al [6] described aspects of the feeding preference of sand ies in the Paci c Honduran area. These authors observed the predominance of Pintomyia (Pifanomyia) evansi and Lutzomyia (Lutzomyia) longipalpis, but couldn't determine the presence of Leishmania (L.) infantum in those species [6].…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Additionally, behavioral characteristics of this species in the study area were described by Carrasco et al [7]. Recently, Mejía et al [6] described aspects of the feeding preference of sand ies in the Paci c Honduran area. These authors observed the predominance of Pintomyia (Pifanomyia) evansi and Lutzomyia (Lutzomyia) longipalpis, but couldn't determine the presence of Leishmania (L.) infantum in those species [6].…”
Section: Resultsmentioning
confidence: 92%
“…Recently, Mejía et al [6] described aspects of the feeding preference of sand ies in the Paci c Honduran area. These authors observed the predominance of Pintomyia (Pifanomyia) evansi and Lutzomyia (Lutzomyia) longipalpis, but couldn't determine the presence of Leishmania (L.) infantum in those species [6]. Similar results were described by Zeledón et al, (1984) and Raymond et al, (2010) who reported those species as the two most common species in areas endemic to NUCL in Costa Rica and Nicaragua, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations